Storage and hydro-priming treatments to improve the seed quality of two traditional rice varieties; Batapola-el and Suwendal, from Sri Lanka - Galappaththi, MO; Jayasuriya, KMGG; Gama-Arachchige, NS (ORYZA-An International Journal of Rice, 2020)
Although the demand for traditional rice varieties has increased, low initial germination and poor storability of these varieties impede its popularization. Thus, the aim of the study was to improve the seed quality using priming treatments and to suggest an effective storage practice of two of the traditional rice varieties; Suwendal and Batapola-el, in Sri Lanka. Seeds were subjected to hydro-priming under various time periods (0, 24, 48 and 72 hours). Seeds were stored in gunny, polysac and polythene bags at room temperature, 25 and 8 °C. Seed quality of primed and stored seeds was evaluated using seed germination, seed vigour (seedling growth and conductivity) and seedling emergence. Hydro-priming for 72 hours has increased the seed germination of the two varieties significantly compared to other priming methods. Further, seeds primed for 72 hours had the highest vigour and highest seedling emergence in both varieties. Storing Suwendal and Batapola-el seeds in polythene bags at 8 °C retained the highest viability and highest vigour for more than six months. Thus, hydropriming for 72 hours could be recommended to enhancethe seed quality of these two tested varieties and storage at 8 °C in sealed polythene bags could be recommended as an effective storage practice to maintain the seed viability till the next sowing season.